Adoption of International Auditing Standard No. 700 and its impact on the auditor’s report on the financial statements (applied research) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The research aims to conduct an analytical comparison of the (updated) International Auditing Standard No. (700), which is concerned with forming the opinion of the external auditor (auditor) and the report on the financial statements issued by the International Federation of Accountants for the year 2010 AD, with the Iraqi Auditing Guide No. (2), which is concerned with the auditor’s report on The financial statements issued by the Accounting and Regulatory Standards Board in the Republic of Iraq in the year 1999, in addition to explaining the impact of adopting and applying International Auditing Standard 700 on the auditor’s report by proposing a proposed model for a local audit guide on the report on financial statements in accordance with international auditing standards.The research reached several conclusions, the most important of which is the clear deficiency in legislation and local audit manuals (Guide No. 2), as it lacks many paragraphs contained in international auditing standards, which may significantly affect the accuracy of the information contained in the external auditor’s report. The research concluded with a recommendation from the bodies regulating the work. The regulatory authority in Iraq, represented by the (Accounting and Regulatory Standards Board), is working to amend Auditing Guide No. (2) related to the auditor’s report on the financial statements, in a manner consistent with the continuous updates and developments of international auditing standards related to the external auditor’s report, with the aim of developing those reports in Iraq and improving its content to become More accurate and useful to beneficiaries.